How to critique a published article. [article]. - Hyman, Ray.
Few replies get published. Many that do get published could be more effective. A reply can be effective only if it is published, readable, and credible. This article suggests guidelines for writing good replies. The guidelines begin with things to keep in mind?for example, that you might be wrong?and things to do before you begin to write. The latter includes considering not responding, considering alternative viewpoints, and distancing yourself from the task. Things to do while writing include using the principle of charity, avoiding ad hominem and emotionally laden arguments, and keeping the rebuttal short. After completing the first draft, you should put it aside for a while as well as get a second opinion. A good reply complements rather than discredits the argument of the target author. --(from the author).